ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI PADI SAWAH SISTEM TABELA DAN TAPIN DI DESA TONGGOLOBIBI KECAMATAN SOJOL KABUPATEN DONGGALA - Erik Pratama; Karlina Muhsin Tondi (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
This study aims to determine the effect of using input production of land area, seeds, urea fertilizer, phonska fertilizer, labor and to analyze the difference in the effect of using the Tapin and Tabela planting methods on the production of lowland rice farming in Tonggolobibi Village, Sojol District, Donggala Regency. Determination of respondents in this study using the stratified random sampling method, with 232 members of the rice farmer population, 117 using the Tablea system and 115 Tapin systems then taking 15 percent samples from each planting system and obtained 37 respondents. The analytical method used in this research is the Cobb-Douglas method. The results showed that the factors of land area, seeds, urea fertilizer, phonska fertilizer, labor and dummy variables (planting system) together (simultaneously) had a significant effect on lowland rice production in Tonggolobibi Village, Sojol District, Donggala Regency. Meanwhile, partially, the variables of land area, urea fertilizer and phonska fertilizer have a significant effect on rice production, except that the variables of seed and labor have no significant effect on lowland rice production. The dummy variable (application of the seed planting system) showed insignificantly different results on lowland rice production in Tonggolobibi Village. This means that the use of one method of planting, both Tabela and Tapin, has not been able to influence changes in lowland rice production